Risk of Melanoma in Patients with Basal Cell Carcinoma: A Population-based Cohort Study - Daniella Kushnir-Grinbaum; Judit Krausz; Nader Rahal; Liat Apel-Sarid; Michael Ziv (Medical Journals Sweden, 2023)
Basal cell carcinoma is the most prevalent cancer in Caucasians worldwide. The aim of this study was to examine the overall risk of melanoma among patients diagnosed with basal cell carcinoma. This population-based retrospective cohort study included data from January 2010 to December 2018 from the databases of the Clalit Health Maintenance Organization and 2 major pathology laboratories in North District, Israel. The incidence and hazard ratio of melanoma in patients with a diagnosis of basal cell carcinoma were determined. Of 466,700 participants, 51% were women and the mean (standard deviation) follow-up was 6.7 (2.9; range 1-9) years. A total of 3,338 patients were diagnosed with basal cell carcinoma during the study period, 82 of whom subsequently developed melanoma. Patients with basal cell carcinoma had a significantly higher incidence of melanoma than patients without basal cell carcinoma (2.46% vs 0.37%; p < 0.0001). Univariate Cox regression analysis revealed a hazard ratio of 6.6 (95% confidence interval: 3.6-12.1; p < 0.0001) for melanoma in patients with a diagnosis of basal cell carcinoma. In conclusion, a diagnosis of basal cell carcinoma confers a significant risk of melanoma.